An Investigation of the Relationship between Earnings Management and Financial Ratios (Panel Data Approach) - Ghyasi, Azar (International Journal of Economics and Financial Issues, 2017)
Earnings management is regarded as conscious actions taken by manager to achieve certain objectives at the framework of accounting procedures. Management, compared to others, has access to information which is not accessible for others. If mangers tend to transmit information introducing actual value of commercial units using earnings management, it is acceptable, however, concern is created when the goal of earnings management is considered as a factor deviating users from information pertaining to the company’s performance. In this regard, this article attempts to investigate the effect of earnings management on some variables such as accounts payable, debt ratio, and gross profit to sale ratio. To this end, data related to companies listed in Tehran stock exchange during 2009-2015 was employed and analysed with the aid of the panel data regression method. According to the research findings, discretionary accruals-based earnings management has the highest effect on accounts payable. Keywords: earnings management, panel data regression, discretionary accrual items JEL Classifications: G, G1, G18